Pengaruh Pemberian Pakan Alami yang Berbeda terhadap Pertumbuhan dan Kelangsungan Hidup Larva Ikan Cupang Hias (Betta splendens) - Armando Oscar Simbolon; Syammaun Usman (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Betta spendens has a really high market price, the successful of betta spendens aquaculture on larvae stage depends of some factor, one of the factor is natural feed feeding in attempt to increase the growth. This research aims to determine of influence of different natural feed feeding towards to increase of growth and survival rate. The method used in this research was randomize complete design with 3 treatment and 3 replication following, T Treatment (Tubifex sp feeding), D treatment (Daphnia sp feeding), dan I Treatment (Infusoria feeding). Data was analyzed with Analysis of Variance (ANOVA) if there is a significant effect will be continue with BNT test. The best growth was on Tubifex sp. treatment with the increase of length from 0.7 cm to 1.7 cm and the growth of weight from 0.03 gr to 0.21 gr.Key Words : Growth, Larvae (Betta splendens), Tubifex sp., Daphia sp., Infusoria